Aspek Hukum Perlindungan Data Konsumen E-Commerce - Ardhiana Hidayah; Marsitiningsih Marsitiningsih (Kosmik Hukum, 2020)
Consumer data protection is part of the consumer protection aspect of online transactions or e-commerce activities. This research is a normative legal research based on library research. This study aims to know and understand that personal data is part of the constitutional rights of citizens, so that the state is obliged to protect dignity, respect and integrity of consumers as human beings. The use of any information through electronic media that involves a person's personal data must be done with the consent of the person concerned. The misuse of consumer data is a major problem in legal protection to consumers. Consumer data protection only relies on Ministerial Regulation Number 20 Year 2016 concerning Protection of Personal Data which cannot be used as a basis for solving the problem of data misuse. There needs to be a special institution in processing law enforcement in the context of protecting consumer data.Keywords: Consumer Data Protection